1990
DOI: 10.1093/oxfordjournals.aje.a115651
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Hepatitis B Virus Among Family Members in the Middle East

Abstract: In 1985, the authors studied the epidemiology of hepatitis B virus (HBV) in a healthy Middle Eastern population. Residents of three remote villages and urban areas of Jordan were assessed for seroprevalence of hepatitis B surface antigen (HBsAg) and HBV infection. Infection was defined as the presence of antibody to hepatitis B core antigen (total) and/or antibody to hepatitis B surface antigen, with or without HBsAg. The overall HBsAg prevalence was 9.9% and was not age-related, although significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
1
4

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 26 publications
5
47
1
4
Order By: Relevance
“…We assessed only a few risk factors for low vaccine coverage and for acquiring chronic HBV infection. Other important factors such as low socioeconomic status and household crowding were not assessed [29][30][31][32][33]. Additionally, small numbers of HBsAg positive children limited stratification by receiving a birth dose and limited evaluation of the impact of ≥3 dose hepatitis B coverage.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed only a few risk factors for low vaccine coverage and for acquiring chronic HBV infection. Other important factors such as low socioeconomic status and household crowding were not assessed [29][30][31][32][33]. Additionally, small numbers of HBsAg positive children limited stratification by receiving a birth dose and limited evaluation of the impact of ≥3 dose hepatitis B coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Other countries (8)(9)(10)(11)(12) have also reported geographical variations of HBsAg seropositivity within their countries. Among them, the study from China (8) showed a higher positivity of HBsAg in coast areas, comparable with ones from Korea.…”
Section: Discussionmentioning
confidence: 99%
“…This decline in the risk of developing the carrier state with increasing age at infection is highly nonlinear and appears to be remarkably consistent for a wide range of communities and geographical settings [18]. Childhood [19,20]. This paper reviews the patterns of HBV infection in highly endemic countries and attempts to define the epidemiological relationships between the routes of infection, the age at infection and the prevalence of carriers.…”
Section: Introductionmentioning
confidence: 89%